Psychotropic prescription: the evaluation of related directions and notifications (Revista Brasileira de Ciências Farmacêuticas, 2004)
The aim of this study was to evaluate the obeying Brazilian Legislation about prescription and dispensation of the psychotropic drugs of lists B and C-1 according to the law 344/98-SVS/MS, based on 753 prescriptions of November 2000 from 7 pharmacies. Disobeying rules by pharmacies was showed in 88.0% from prescriptions B, and in 85.0% from C1, while this percentage was of 99.6% from B and 96.5% from C1 among the doctors. The most important failures observed on prescriptions were: absence of patient address (92.6% from B and 80.1% from C1); absence of the quantity dispensed (85.5% from B and 72.6% from C1); absence of the quantity prescribed. Medicine dispensation occurred correctly in the period of time fixed by law in 89.2% from B, and in 57.1% from C lists. Anorexigens predominated among the prescriptions B (52.3%) followed by benzodiazepines (47.7%). Fluoxetin was predominant among prescriptions C1 (68.8%), followed by amytriptilin (12.5%). Prescriptions were mostly emitted by general clinicians (51.4%). The results showed inadequate practices concerned to the controlled drugs prescription and delivery, confirming the necessity of a better fiscalization.